Pengaruh Pengendalian Internal Terhadap Pencegahan Fraud di Rumah Sakit (Studi Empiris pada Rumah Sakit Swasta di Jabodetabek) - Dwi Zarlis (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
This study examined and proved the influence of internal control against fraud in the hospital either simultaneously or partially. This study used a questionnaire survey with 86 respondents taken from 10 hospitals  in  Jabodetabek.  Statistical  tests using  simultaneous  significance test  ( F test ) shows the influence of the independent variables with the same independent variable. While significant partial test (t test) showed that the control environment, risk assessment, control activities, information and communication, and monitoring have t results > t table at a significance level of 5%, so  partially significant effect have a value < 0.05.